Feeding habit of yellowfin black seabream, acanthopagrus latus in hiroshima bay - Norshida, Ismail; Ahmad Syazni, Kamarudin (2016)
Yellowfin black seabream, Acanthopagrus latus is a common Sparidae fish inhabiting Hiroshima Bay. In addition, Black seabream, Acanthopagrus schlegelii is a closely related species to A. Latus with the long history of stock enhancement especially in Hiroshima Bay and Japan in general. Hence. this study aims to contribute fundamental information on feeding habits and species management that can help maintaining sustainable fisheries in Hiroshima Bay. A total number of 324 alimentary tracts were removed from individuals sampling starting in March 2011 until February 2012 from Kusatsu fish market and angling tournament. The stomach was cut, and its content was then transferred into a petri dish and prey items were then sorted, counted, wet weighed and identified to the lowest possible taxonomic level. From the total 324 stomachs examined, 1 14 of them were empty (35.2 %). The vacuity coefficient varied significantly between season (Chi square, x2 = 9.271, p < 0.05). A total number of 25 prey items have been identified. Overall index of equitability value (E=0.5l ) for all specimens suggested that a few prey items dominated the diet of A. lotus in Hiroshima Bay. The Spearman rank correlation coefficient showed that the diet composition between 1 to 3 year classes and > 8 years class were not significantly correlated. The index of relative importance, !Ri % obtained in the present study demonstrated that the diet composition of A. lotus in Hiroshima Bay was mainly composed of polychaetes, bivalves and dccapods. Different prey preferences by other Sparidae fish mostly in Hiroshima Bay will at least reduce the competition for feeding.